A method for regulating the soil micro-ecological environment for tobacco planting using silicon fertilizer and micronutrients

CN122977903APending Publication Date: 2026-10-27LINCANG OF YUNNAN TOBACCO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610915768.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-24
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0003]一方面,现有硅肥(如普通硅酸钠水溶肥或矿渣型硅肥)及常规中微量元素无机盐肥施入土壤后释放过快,由于植烟土壤多呈酸性(pH 4.5至5.5),速效释放的有效硅会迅速与土壤中的铝、铁离子反应生成难溶性沉淀,而游离态的锌、锰等离子也极易被土壤氧化物吸附固定或与磷酸根形成沉淀,导致有效态养分转化效率及当季利用率极低

Benefits of technology

[0017]本发明提供的一种利用硅肥和中微量元素调控植烟土壤微生态环境的方法,至少具备以下有益效果:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

This invention relates to a method for regulating the microecological environment of tobacco-growing soil using silicon fertilizer and trace elements, belonging to the field of agricultural fertilizer and soil conditioning technology. Addressing the problems of rapid release and easy fixation and inactivation of existing silicon fertilizers and trace elements in acidic tobacco-growing soils, this invention uses a sol-gel method as its core. Water glass is purified by acid-catalyzed hydrolysis and sodium removal, and then co-deposited in situ with citric acid-chelated zinc and manganese, molecular boric acid, and lightly calcined magnesium oxide in a silica mesoporous gel framework via alkali-catalyzed condensation. After aging, drying, and granulation, composite conditioner particles are obtained. When these particles are applied to acidic soil, the gel framework gradually dissolves, simultaneously releasing effective silicon and trace elements. The hydration and alkali release of magnesium oxide synergistically increases soil pH, promotes the transformation of the rhizosphere microbial community into a bacterial type, and improves the quality of flue-cured tobacco.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of agricultural fertilizer and soil conditioning technology, and in particular to a method for regulating the micro-ecological environment of tobacco-growing soil using silicon fertilizer and trace elements. Background Technology

[0002] The quality and yield of flue-cured tobacco are highly dependent on the physicochemical properties and microecological environment of the planting soil. In existing flue-cured tobacco cultivation processes, the supplementation of silicon fertilizer and micronutrients (zinc, manganese, boron, etc.) is crucial for improving the stress resistance of tobacco plants and enhancing the quality of the upper leaves. However, the application of silicon fertilizer and micronutrients in current technologies presents two prominent problems:

[0003] On the one hand, existing silicon fertilizers (such as ordinary sodium silicate water-soluble fertilizer or slag-type silicon fertilizer) and conventional trace element inorganic salt fertilizers release silicon too quickly after being applied to the soil. Since tobacco-growing soils are mostly acidic (pH 4.5 to 5.5), the rapidly released available silicon quickly reacts with aluminum and iron ions in the soil to form insoluble precipitates. Meanwhile, free zinc and manganese ions are also easily adsorbed and fixed by soil oxides or form precipitates with phosphate ions, resulting in extremely low efficiency of available nutrient conversion and utilization rate in the current season. The low nutrient utilization rate forces the application of fertilizers to continuously increase, and this vicious cycle of "rapid release - easy fixation - forced increase" further exacerbates soil acidification.

[0004] On the other hand, the exacerbation of soil acidification directly leads to the degradation of the soil microecological environment, manifested as an increase in the relative abundance of harmful fungi, a decrease in the abundance of beneficial bacteria, and a reduction in the diversity of rhizosphere microbial communities. This, in turn, results in quality defects such as hindered root absorption in tobacco plants, difficulty in ripening and yellowing of upper tobacco leaves, and noticeable green and off-flavors. Current technologies typically treat the application of silicon fertilizer and the supplementation of micronutrients as independent physical mixing steps, failing to systematically integrate nutrient slow release and soil pH regulation from the source of fertilizer preparation chemical processes. This lack of integration prevents the establishment of a multi-component synergistic mechanism at the molecular scale, making it difficult to truly solve the technical problems of soil microecological degradation and declining tobacco quality. Summary of the Invention

[0005] To address the aforementioned technical problems, this invention provides a method for regulating the micro-ecological environment of tobacco-growing soil using silicon fertilizer and trace elements, comprising the following steps: providing an aqueous solution of silicon source; adding an acidic catalyst under stirring conditions to carry out an acid-catalyzed hydrolysis reaction; subsequently removing the byproduct salts generated by hydrolysis to obtain a low-sodium silicate gel primary suspension; mixing and reacting zinc, manganese, and boron sources with a chelating agent in an aqueous solvent to prepare a trace element chelate solution; adding the trace element chelate solution to the low-sodium silicate gel primary suspension under heating and stirring conditions and mixing evenly, then adding lightly calcined magnesium oxide powder in batches, followed by adding an alkaline regulator to adjust the pH value of the system for alkaline catalysis. A condensation reaction is carried out, in which chelated zinc and manganese, molecular boric acid, and lightly calcined magnesium oxide are co-deposited in situ and embedded into the three-dimensional network framework of the silica mesoporous gel generated with the reaction, resulting in a gel transformation to obtain a gel body. The gel body is then subjected to aging treatment, drying, and granulation to obtain silicon-based micronutrient composite conditioner particles. During the flue-cured tobacco planting stage, the silicon-based micronutrient composite conditioner particles are applied as base fertilizer and / or top dressing to acidic tobacco-growing soil. Through the gradual dissolution of the silica gel framework under acidic conditions, the effective silicon, chelated zinc and manganese, and molecular boron are released simultaneously and slowly, thereby regulating the pH and microecological environment of the tobacco-growing soil. This invention utilizes a series of chemical reactions—acid-catalyzed hydrolysis, neutralization and desodium removal, alkali-catalyzed condensation and in-situ co-deposition—to physically encapsulate and chemically bind chelated nutrients through a gel skeleton. This allows nutrients to be gradually released as the gel skeleton hydrolyzes and breaks down under acidic soil conditions, fundamentally preventing the rapid fixation and inactivation of fast-acting fertilizers in the soil.

[0006] According to a preferred embodiment of the present invention, in the acid-catalyzed hydrolysis reaction, the silicon source aqueous solution is a water glass dilution with a silica mass concentration of 10% to 12%; the acid catalyst is preferably hydrochloric acid, which is slowly added to lower the pH of the system to 1.5 to 2.5. The reason for controlling the hydrolysis pH to 1.5 to 2.5 is that this range is near and below the isoelectric point of silicic acid (approximately pH 2 to 3), and the acid-catalyzed and base-catalyzed rates of the silanol condensation reaction are both at their minimum values ​​within this range. The silica sol particles exhibit significant kinetic stability due to the extremely slow condensation reaction, and can maintain the dispersed state of the sol within the operating time window. If the pH is higher than 3.0, the base-catalyzed condensation rate increases sharply, which will trigger uncontrollable local gelation, resulting in an uneven product skeleton structure. If the pH is too low (e.g., below 1.0), silica is very likely to precipitate directly instead of forming a uniform sol.

[0007] More preferably, the process of removing byproduct salts generated by hydrolysis includes: adding anhydrous ethanol to the hydrolyzed system to promote moderate aggregation of the silica gel primary particles; retaining the solid after solid-liquid separation; and washing the solid with deionized water until the washing liquid is free of chloride ions. The purpose of adding anhydrous ethanol is to reduce solvent polarity, enhance the hydrogen bonding between the silanol groups on the surface of the silica sol particles, promote moderate aggregation of the particles to form a loose gel for easy filtration and separation, and simultaneously retain the byproduct sodium chloride in the liquid phase. Subsequent thorough washing with water can completely remove sodium ions. If the residual sodium ions in the product are too high, application to the soil will lead to soil compaction and an increased sodium exchange ratio, causing severe osmotic stress on the roots and microorganisms of flue-cured tobacco.

[0008] According to another aspect of the present invention, in preparing the trace element chelating solution, the chelating agent is preferably citric acid, the zinc source is zinc sulfate, the manganese source is manganese sulfate, and the boron source is boric acid. Preferably, the molar ratio of citric acid to the total molar amount of zinc and manganese ions is controlled to be between 1.2:1 and 1.5:1. The reason for controlling this molar ratio is that citric acid molecules can form stable five-membered chelate rings with zinc and manganese ions through multidentate coordination, allowing the metal ions to remain in a dissolved state over a wide pH range; if the molar ratio is lower than 1.2:1, incomplete chelation will result, and hydroxide precipitates will easily form and block the pores in the subsequent alkaline polycondensation stage; if the molar ratio is higher than 1.5:1, excess free citric acid will increase production costs and may interfere with the subsequent condensation reaction of silanol groups.

[0009] According to another aspect of the present invention, during the alkaline-catalyzed polycondensation reaction stage, the system temperature under the heating and stirring conditions is maintained at 55°C to 65°C. The reason for controlling the temperature at 55°C to 65°C is that this temperature range provides suitable activation energy to accelerate the polycondensation rate of monosilicic acid, while simultaneously promoting coordination exchange between citric acid chelated metal ions and silanol groups on the surface of the silica gel. If the temperature is below 55°C, the polycondensation reaction and gelation process are extremely slow, leading to the back diffusion of chelated metal ions into the liquid, thereby reducing the uniformity of the composite. If the temperature is above 65°C, the thermal decomposition rate of the citric acid chelate complex is significantly accelerated, and the released free metal ions rapidly form hydroxide precipitates, disrupting the uniformity of nutrient distribution in the product.

[0010] More preferably, the alkaline regulator is ammonia water, which is used to precisely adjust the pH of the system to 5.0 to 5.5, and the mixture is continuously stirred at the above temperature for 2 to 3 hours to carry out polycondensation. Controlling the polycondensation pH to 5.0 to 5.5 is the core of regulating the mesoporous structure and the nutrient slow-release rate. Within this pH window, the polycondensation rate is moderate, which can form a branched three-dimensional network structure and give the material an ideal mesoporous size. If the pH is below 5.0, the polycondensation reaction is too slow, and the resulting gel skeleton is too loose (pore size greater than 12 nm), resulting in nutrient release too quickly after application and loss of slow-release function. If the pH is above 5.5, the polycondensation is too fast, which will lead to an excessively dense gel skeleton (pore size less than 3 nm), which will not only excessively lock in nutrients and fail to meet the seasonal needs of flue-cured tobacco, but also increase the risk of local hydroxide precipitation.

[0011] More preferably, during the co-deposition process, the particle size of the lightly calcined magnesium oxide powder is such that it passes through a 200-mesh sieve, and its total addition is controlled to be 25% to 42% of the mass of silica contained in the initial silicon source aqueous solution. In the system, the lightly calcined magnesium oxide partially hydrates into magnesium hydroxide nanosheets, whose edge hydroxyl groups condense with adjacent silanol groups to form magnesium-silicon composite nodes, thereby physically embedding and chemically bonding them into the gel framework, endowing the material with good pH buffering properties. If the addition amount is less than 25%, the product's alkali release capacity is insufficient, and it cannot effectively raise the pH value of acidic soils; if the addition amount is greater than 42%, a large number of sheet structures will compete for the nucleation sites of the silica gel, disrupting the continuity of the three-dimensional network framework, leading to gel fragmentation and loss of sustained-release capacity.

[0012] According to another aspect of the present invention, the aging treatment conditions are preferably as follows: the gel that has undergone gelation transformation is placed in an environment of 55°C to 65°C and allowed to stand for aging for 12 to 18 hours, so that the specific surface area of ​​the silica mesoporous gel is stabilized at 180 m². 2 / g to 280 m 2 / g, with mesopore sizes ranging from 4 nm to 8 nm. The purpose of aging treatment is to utilize the Ostwald ripening mechanism to dissolve and redeposit smaller silica particles in the framework onto the surface of larger particles, thereby increasing the framework wall thickness, narrowing the pore size distribution, and ensuring that the product has a stable and predictable dissolution rate in the soil environment.

[0013] More preferably, the drying process employs a gradient heating method, i.e., the aged gel is first broken up and then pre-dried at 60°C for 6 to 8 hours, followed by heating to 105°C and drying to constant weight. The reason for the low-temperature, slow pre-drying is that the gel channels contain a large amount of moisture, and direct high-temperature baking would cause intense capillary forces, leading to severe shrinkage and collapse of the three-dimensional framework and destruction of the mesoporous structure.

[0014] More preferably, the granulation process includes: uniformly premixing sodium carboxymethyl cellulose powder and composite conditioner powder, then wet granulating the premixed powder using deionized water as a wetting agent. After absorbing water and swelling, sodium carboxymethyl cellulose forms in-situ polymer bridges, causing the powder to nucleate and spherize. The total amount of sodium carboxymethyl cellulose solid is controlled to be 1% to 3% of the mass of the composite conditioner powder. This dosage range ensures that the powder can successfully nucleate and spherize under droplet wetting, forming particles with sufficient strength, while avoiding excessive polymer binder coating the particle surface, thus blocking mesoporous channels and hindering nutrient release.

[0015] Ideally, the application process during the tobacco planting stage is divided into two phases: the first phase is basal fertilizer application, which is carried out 7 to 10 days before transplanting, with the conditioner granules rotary tilled into the topsoil at a rate of 40 to 60 kg per acre to a depth of 0 to 20 cm; the second phase is topdressing application, which is carried out 30 days after transplanting, during the seedling stage, with the conditioner applied in furrows between the tobacco plants at a rate of 15 to 20 kg per acre. This application strategy perfectly matches the continuous demand for micronutrients from the "vigorous growth stage to maturity stage" of flue-cured tobacco, eliminating the need for any additional inorganic silicon fertilizer or micronutrient fertilizer during the entire growth period.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] The present invention provides a method for regulating the micro-ecological environment of tobacco-growing soil using silicon fertilizer and trace elements, which has at least the following beneficial effects:

[0018] This invention significantly improves the seasonal utilization efficiency of available silicon and trace elements. It constructs a three-dimensional network of mesoporous silica gel using a sol-gel chemical process, embedding zinc and manganese in molecularly dispersed chelated states and boron in molecular boric acid form within the framework channels. This composite structure exhibits a slow-dissolution characteristic in acidic soils based on the breaking of silicon-oxygen bonds, resulting in a significant reduction in the release rate of available silicon and trace elements. This fundamentally blocks the pathway by which conventional fertilizers, due to their rapid release, easily combine with soil oxides and phosphates to form ineffective precipitates.

[0019] This synergistic process achieves continuous buffering and regulation of pH in acidic tobacco-growing soils and restoration of the microecological environment. The silicon-based conditioner prepared in this invention undergoes a reverse hydrolysis-dissolution reaction in the soil, continuously consuming hydrogen ions, while the lightly calcined magnesium oxide component embedded in the framework simultaneously hydrates and releases hydroxide ions. These two factors work synergistically to ensure that the rhizosphere pH of the tobacco-growing soil within the fertilization zone steadily increases and remains within a more suitable slightly acidic range throughout a growing season, avoiding the drastic pH fluctuations caused by conventional lime-based materials. The alleviation of soil acid stress indirectly promotes the transformation of the rhizosphere microbial community towards a healthy "bacterial" type, which is beneficial for increasing the abundance of beneficial bacteria and inhibiting the reproduction of pathogenic fungi.

[0020] This invention improves the agronomic traits and upper leaf quality of flue-cured tobacco from the source. The "slow-release nutrient supply-microecological improvement" linkage mechanism established in this invention significantly alleviates aluminum toxicity stress and restores the root vitality of tobacco plants. The continuous supply of effective silicon enhances the stress resistance of tobacco plants, while the stable release of chelated trace elements and magnesium ions promotes the photosynthetic carbon and nitrogen metabolism balance of leaves. Applying the compound conditioner prepared by the method of this invention can objectively improve the leaf opening degree of upper tobacco leaves, optimize the sugar-alkali ratio, and reduce the raw and unpleasant odors in the final sensory evaluation, effectively solving the problem of tobacco leaf quality decline caused by soil degradation under conventional fertilization mode. Detailed Implementation

[0021] The present invention will now be described in detail with reference to specific embodiments and comparative examples. The following embodiments are for illustrative purposes only and should not be construed as limiting the scope of the invention. Unless otherwise stated, the reagents and instruments used in the embodiments are all commercially available conventional products, and the operating methods used are all conventional methods in the art.

[0022] This invention provides a method for regulating the micro-ecological environment of tobacco-growing soil using silicon fertilizer and trace elements. The overall technical concept is as follows: using a sol-gel chemical reaction as the core process route, in a two-step controllable reaction process of acid-catalyzed hydrolysis and alkali-catalyzed condensation, an industrial water glass silicon source is in situ transformed into a three-dimensional network framework of silica gel with a mesoporous structure. Simultaneously, during the gelation stage, citric acid-chelated Zn... 2+ and Mn 2+ Molecular-state H3BO3 and lightly calcined magnesium oxide micropowder were embedded in the gel channels and framework nodes through in-situ co-deposition. After aging, gradient drying, and wet granulation, a functional silicon-based trace element composite conditioner particle with pH-responsive slow-release characteristics was prepared. When this particle was applied to acidic tobacco-growing soil, the Si-O-Si bonds in the gel framework were broken down by H3BO3 in the acidic soil environment (pH 4.5–5.5). + Catalytic reverse hydrolysis and dissolution occur (≡Si-O-Si≡ + H₂O → 2≡Si-OH → H₄SiO₄), a process that directly consumes H₂O. + This process gradually increases the pH of the rhizosphere microdomain; simultaneously, the dissolution releases chelated Zn, Mn, and molecular B(OH)3 anchored to the inner wall of the gel channels via weak coordination bonds (Si-O···M, M = Zn, Mn, Mg), achieving the simultaneous and sustained release of effective silicon and trace elements; the lightly calcined magnesium oxide component embedded in the framework hydrates to Mg(OH)2 and further releases OH. -This provides a secondary pH buffer. The synergistic effect of these three factors steadily increases the pH of the rhizosphere microenvironment of tobacco-growing soil within the fertilization zone by 0.2–0.5 units over a complete growing season (approximately 120 days), effectively alleviating aluminum toxicity stress and indirectly promoting the transformation of the rhizosphere microbial community from a "fungus-dominant" type represented by Fusarium to a "bacterial-dominant" type represented by Bacillus and Pseudomonas, thereby fundamentally improving the agronomic traits and upper leaf quality of flue-cured tobacco.

[0023] The chemical reaction basis of the above technical concept is as follows. The first stage is acid-catalyzed hydrolysis. Water glass (Na₂O·nSiO₂, n = 3.1~3.4) undergoes the following reaction under hydrochloric acid acidification: Na₂O·nSiO₂ + 2HCl + (2n-1)H₂O → nSi(OH)₄ + 2NaCl. In this reaction, H₂O… + As a catalyst, water molecules attack the Si-O-Si bridging oxygen atoms in the polysilicate chain, polarizing the Si-O bond and lowering its bond energy. Water molecules then nucleophilically attack the silicon atoms, completing hydrolysis and breaking the bond, ultimately degrading the highly polymerized sodium polysilicate into orthosilicate Si(OH)4 monomer. From the above stoichiometric relationship, it can be seen that 2 moles of HCl are needed to neutralize each mole of Na2O to eliminate the alkalinity of the water glass. Taking the preferred SiO2 concentration of 11% (approximately 110 g SiO2 / 1000 g working solution) and modulus n = 3.2 as an example, 110 g SiO2 corresponds to approximately 1.83 mol SiO2, and the corresponding amount of Na2O is 1.83 / 3.2 ≈ 0.57 mol. Theoretically, neutralizing this amount of alkali requires approximately 1.14 mol of HCl (i.e., 570 mL of 2 mol / L hydrochloric acid working solution). In addition, a small amount of hydrochloric acid is needed to further lower the system from neutral to the target pH of 1.5–2.5. The chemical basis for controlling the final pH of hydrolysis within the range of 1.5–2.5 is that this pH range is precisely near and below the isoelectric point of silicic acid (pH ≈ 2–3). Under these conditions, silanol groups (≡Si-OH) hardly ionize, while acid-catalyzed condensation (requiring H+) occurs. + The rate of attack on bridging oxygen atoms is related to the base-catalyzed polycondensation (requiring OH groups). - The rate of nucleophilic attack on silicon atoms is at a minimum near the isoelectric point, and the kinetic energy barrier for dehydration condensation between silanol groups is the highest. Therefore, although the net surface charge of silica sol particles is close to zero and they lack strong electrostatic repulsion, they exhibit significant "kinetic stability" due to the extremely slow condensation reaction rate, which is sufficient to maintain the dispersion of the sol within an operating time window of several hours. Once the pH exceeds this range (pH > 3.0), the alkali-catalyzed condensation rate increases sharply (the rate constant is related to [OH]). -The pH value is directly proportional to the H+ level, which will trigger uncontrollable particle aggregation and localized gelation, disrupting the uniformity of subsequent processes. Conversely, if the pH is too low (< 1.0), excessively high H+ will cause uncontrollable particle aggregation and localized gelation, disrupting the uniformity of subsequent processes. + The concentration will cause Si(OH)4 to undergo excessive dehydration, precipitating directly as amorphous SiO2 instead of forming a homogeneous sol. Therefore, pH 1.5–2.5 is the optimal window to balance complete hydrolysis and sol kinetic stability. A stirring rate of 250–300 rpm ensures that the hydrochloric acid droplets are uniformly dispersed within 0.5 s after entering the water glass surface, avoiding SiO2 precipitation instead of sol formation due to localized over-acidity (pH < 1.0).

[0024] The second stage is the sodium removal process. The NaCl produced as a byproduct of the hydrolysis reaction must be completely removed before the polycondensation step because: (1) Na + When products with excessive residual content (> 2 wt%) are applied to the soil, the soil exchangeable sodium ratio (ESP) will increase, causing soil particle dispersion, pore blockage and compaction, which will cause osmotic stress on the roots of flue-cured tobacco; (2) The presence of NaCl will change the ionic strength and electrostatic interaction between the particles in the subsequent condensation stage, interfering with the controllable growth of the gel skeleton structure. The present invention uses anhydrous ethanol (volume ratio 0.3:1 to 0.5:1) to be added to acidic silica sol to achieve liquid-solid separation: ethanol reduces the polarity of the solvent, which enhances the hydrogen bonding between the silanol groups (≡Si-OH) on the surface of the silica sol particles, and the particles will aggregate moderately to form a loose gel primary body network that can be filtered and retained, while NaCl remains in the filtrate because it still maintains good solubility in the ethanol-water mixed solvent. It is important to note that the "primary gel" formed here is a physical aggregate, meaning that hydrogen bonds (bond energy approximately 15–25 kJ / mol) between silanol groups are the main cross-linking force. Although its three-dimensional network structure has sufficient mechanical strength to maintain the integrity of the filter cake under filtration conditions, large-scale covalent Si-O-Si condensation reactions have not yet occurred between particles at the molecular scale. When this physical aggregate is subsequently redispersed in deionized water, it can be restored to a metastable concentrated silica gel suspension (solid content approximately 15%–20%) by stirring (200–250 rpm), providing a uniformly dispersed silicon source precursor for the fourth-stage alkali-catalyzed polycondensation reaction. It should be noted that true, irreversible chemical gelation (the formation of the covalent Si-O-Si three-dimensional network) occurs during the fourth-stage alkali-catalyzed polycondensation process. The primary gel filter cake was subsequently washed three times with deionized water (800 mL each time). A polypropylene filter membrane with a pore size of 10–20 μm was used, and the pressure difference during filtration was controlled to be ≤ 30 kPa to avoid excessive flow rate dispersing the filter cake structure. The concentration gradient-driven diffusion-osmosis process was utilized to remove residual Na+ from the gel channels. + and Cl -Elute to trace levels (the endpoint is reached when no white precipitate is detected in the washing solution with AgNO3 reagent, i.e., Cl). - The concentration was approximately 0.01 mmol / L below the detection limit. Although the restoration of solvent polarity during pure water washing carries a theoretical risk of peptization of the nano-silica particles, the rigidity of the network skeleton has significantly increased because the primary gel network in the filter cake has undergone further densification and aging during filtration (i.e., some silanol groups spontaneously condense into Si-O-Si bonds under close contact). In practice, the filter cake can maintain its structural integrity without significant depolymerization during three water washes.

[0025] The third stage involves the preparation of a trace element chelating solution (containing chelated zinc and manganese, and dissolved boric acid). This invention uses citric acid (H3Cit) as the chelating agent. Its molecular structure contains three carboxyl groups (-COOH) and one α-hydroxyl group (-OH), allowing it to coordinate with Zn through multidentate coordination. 2+ Mn 2+ Each forms [Zn(Cit)] - (lgK_stability = 4.98) and [Mn(Cit)] - The (lgK_stable = 3.67) type chelate complex coordinates with the metal ion via two carboxyl oxygen groups and one hydroxyl oxygen group, forming a thermodynamically favorable five-membered chelate ring. This chelate protection endows the metal ion with the ability to maintain its dissolved state without hydroxide precipitation over a wide pH range of 1.0–7.0. This is crucial for preventing Zn(OH)₂ (K_sp = 3.0 × 10⁻⁶) from precipitating after the pH of the system is adjusted to 5.0–5.5 in step four. -17 ) and Mn(OH)2 (K_sp = 2.0×10 -13 Precipitation and blockage of the mesoporous channels of the gel are crucial. The molar ratio of citric acid to zinc and manganese ions is controlled at 1.2:1 to 1.5:1 to ensure sufficient coordination of each metal ion with citric acid, achieving a chelation completeness > 98% (verified by ion chromatography determination of residual free metal ions). Boric acid exists primarily as undissociated B(OH)3 molecules (pKa = 9.24) within the above pH range and does not form chelates with citric acid. However, it can be anchored to the inner wall of the gel channels during subsequent polycondensation through hydrogen bonding adsorption between B(OH)3 molecules and silanol groups on the surface of the silica gel framework (B-OH···HO-Si≡). Simultaneously, during the gelation process, it is physically embedded in the mesoporous channels by the three-dimensional network framework, thus achieving effective retention of boron in the product.

[0026] The fourth stage, alkali-catalyzed polycondensation and in-situ co-deposition, is the core reaction stage of this invention. The low-sodium silicate primary suspension is heated to 55–65°C, then a trace element chelating mother liquor and lightly calcined magnesium oxide powder are introduced. The pH of the system is then precisely adjusted to 5.0–5.5 with ammonia. Under these temperature and pH conditions, stirring is continued for 2–3 hours to induce alkali-catalyzed polycondensation. The core chemical reaction is the dehydration condensation of orthosilicic acid: ≡Si-OH + HO-Si≡ → ​​(OH-) - (Catalysis) → ≡Si-O-Si≡ +H₂O. The base catalytic mechanism is OH⁻. - As a nucleophile, it attacks electron-deficient silicon atoms, forming a five-coordinate transition state [Si(OH)5]. - Subsequently, this transition state undergoes dehydration condensation with another silanol group to form a siloxane bond. Within a pH window of 5.0–5.5, the polymerization rate is moderate, resulting in a branched three-dimensional network structure in the gel framework, imparting a mesoporous pore size distribution of 4–8 nm to the material. The choice of temperature 55–65 °C is based on Arrhenius kinetics: the apparent activation energy of the silanol condensation reaction is approximately 60–70 kJ / mol, and within this temperature window, the reaction rate is sufficient to complete the gelation transition within 2–3 hours. Simultaneously, this temperature is below the significant thermal decomposition temperature (>80 °C) of the citric acid chelate complex, ensuring the stability of the chelated metal ions throughout the polymerization process.

[0027] The batch addition of lightly calcined magnesium oxide and the subsequent pH adjustment with ammonia water in this stage need to be understood in conjunction with the complete acid-base balance of the system. After the trace element chelate mother liquor is introduced into the low-sodium silicate gel suspension, the main acid sources in the system include three parts: (1) the multi-stage buffering capacity provided by citric acid, whose three dissociation constants are pKa1 = 3.13, pKa2 = 4.76 and pKa3 = 6.40, respectively. During the titration from low pH to pH 5.0 to 5.5, the first and second stage protons are basically completely released, and the third stage protons are partially released. Therefore, each mole of citric acid can provide about 2.0 to 2.1 equivalents of titratable acidity in this pH range; (2) a large number of silanol groups (≡Si-OH) on the surface and inside of the silica gel primary body, whose pKa value is about 4 to 7 (depending on the type of silanol). During the process of pH rising from acidic to 5.0 to 5.5, deprotonation gradually occurs, providing significant additional buffering capacity for the system. Based on 110 g SiO2 (1.83 mol SiO2), the amount of titratable silanol groups in the loose gel primary network that has not been fully condensed is about 0.4 to 0.6 mol equivalents; (3) a small amount of free acid released by the metal chelation reaction. Taking Example 1 as an example, when about 0.56 mol of citric acid in the system provides about 1.15 mol of buffer acidity, plus about 0.5 mol of buffer acidity provided by silanol groups and residual free acidity, the total titratable acidity of the system is about 1.7 mol equivalents. And 38 g of lightly calcined magnesium oxide (85% purity, about 0.80 mol MgO) can theoretically provide 1.60 mol of base equivalents. Therefore, the base amount of MgO is roughly matched with but slightly lower than the total acid buffer capacity of the system. After MgO is added in batches, the pH of the system is gradually raised to about 4.5 to 5.0. Ammonia solution (approximately 80–90 mL of 1 mol / L working solution, providing approximately 0.08–0.09 mol alkali equivalent) was used for precise fine-tuning to stabilize the final pH within the target window of 5.0–5.5. It is worth noting that although lightly calcined magnesium oxide is a strongly alkaline oxide, its dissolution process is controlled by solid-liquid interface reaction kinetics. The dissolution of 200-mesh powder under stirring conditions is not instantaneous, but rather the dissolution driving force decreases as the system pH gradually increases. Specifically, as the pH increases, [H... +As the concentration decreases, the acid dissolution rate of MgO slows down accordingly. Simultaneously, under conditions of 55–65℃ and pH > 4.0, the condensation reaction of orthosilicic acid has already begun, and the forming gel network physically encapsulates the incompletely dissolved MgO powder, further limiting its subsequent dissolution rate. Therefore, in actual operation, the release of alkali from MgO is gradual, avoiding a sudden rise in pH to the strongly alkaline range caused by a single release of all alkali. The batch feeding strategy (1 / 3 to 1 / 4 of the total amount each time, with 5-minute intervals) is precisely to utilize this kinetic controllability, ensuring that each batch of MgO has sufficient time to be absorbed by the system buffer.

[0028] During the polymerization process, chelated Zn and Mn are anchored to the inner wall of the gel channels through the following coordination exchange reaction: ≡Si-OH + [Zn(Cit)] - → ≡Si-O···Zn(Cit) + H + The weak coordination bond (bond energy approximately 40–60 kJ / mol, far lower than the approximately 450 kJ / mol of the Si-O-Si covalent bond) ensures that the chelated nutrients are both bound by the gel framework and prevented from being released explosively at the beginning of fertilization, and are not excessively blocked so as not to be released during framework dissolution. At the same time, the lightly calcined magnesium oxide micropowder partially hydrates into Mg(OH)2 nanosheets at 55–65 °C. The edge hydroxyl groups of these nanosheets undergo a condensation reaction with adjacent silanol groups (Mg-OH + HO-Si≡ → ​​Mg-O-Si≡ + H₂O), forming magnesium-silicon composite framework nodes. This anchors MgO / Mg(OH)2 in the gel network in a dual manner of physical embedding and chemical bonding.

[0029] The fifth stage is gel aging. After gelation, the gel is allowed to stand at 55–65°C for 12–18 hours. Utilizing the Ostwald ripening mechanism, the thermodynamically unstable smaller silica particles (small radius of curvature, high surface energy) in the framework dissolve and redeposit on the surface of particles with larger radii of curvature, thereby increasing the framework wall thickness and narrowing the mesopore size distribution. The physicochemical marker of the aging endpoint is a stable specific surface area of ​​180–280 m². 2 / g and the full width at half maximum (FWHM) of the pore size distribution narrows to ≤ 3 nm.

[0030] The sixth stage is gradient drying and granulation. The drying process employs a gradient heating method, first at low temperature (60℃, 6-8 hours) and then at high temperature (105℃ to constant weight). The chemical engineering principle behind this is that the gel skeleton contains a large amount of capillary water within its pores. The Young-Laplace equation indicates that the smaller the radius of curvature of the pores, the greater the capillary pressure (ΔP = 2γcosθ / r). Direct high-temperature baking will cause the water in the small pores to vaporize rapidly, generating enormous stress, leading to skeleton collapse and destruction of the mesoporous structure. The initial low-temperature drying stage removes most of the free water and capillary water in the large pores at a slow rate, allowing the skeleton to shrink to a basically stable state under low stress conditions. Then, the temperature is increased to remove residual water in the small pores. It should be noted that because ammonia is used as an alkaline regulator in step S3, NH3·H2O will decompose and escape during the drying stage (especially in the 105℃ high-temperature section), causing the pH of the pore liquid to shift towards acidity. However, this shift does not affect the final performance of the product because: (1) the three-dimensional Si-O-Si covalent network of the gel skeleton has been fully formed in the fourth stage of alkaline catalytic polycondensation, and its structural stability depends on the covalent bonds rather than the ambient pH; (2) the chelated metal ions are anchored to the skeleton through Si-O···M coordination bonds, and the thermodynamic stability of these bonds is mainly controlled by coordination chemistry; (3) most of the free water and dissolved NH3 have been slowly discharged during the initial drying stage at 60℃. When the temperature rises to 105℃, the remaining water is mainly capillary water and a small amount of adsorbed water. The system has essentially left the solution state and no longer has the traditional concept of "pH". After the dried product is crushed through a 100-mesh sieve, it is wet granulated using sodium carboxymethyl cellulose (CMC-Na) as a binder. The specific operation is as follows: First, CMC-Na dry powder and composite conditioner powder are premixed in a V-type mixer for 10 minutes to ensure the binder is evenly dispersed in the powder. Then, the premixed powder is transferred to a disc granulator, using deionized water as a wetting agent and continuously sprayed through a dual-fluid nozzle, controlling the total liquid-to-solid mass ratio to be 0.20:1 to 0.25:1 (i.e., 200 to 250 mL of water per 1000 g of powder). During the granulation process, CMC-Na dry powder absorbs water and swells, forming viscous polymer bridges in situ, causing the powder particles to nucleate and become round. The amount of CMC-Na used is controlled at 1% to 3% of the dry powder mass. The long-chain polymers of CMC-Na form polymer bridges after wetting the surface of the powder particles, improving particle strength; however, excessive use will result in an excessively thick polymer film that blocks the entrance to the mesoporous channels, hindering the penetration of soil water into the gel skeleton and reducing nutrient release efficiency.

[0031] The specific operations and results of each embodiment and comparative example are described in detail below.

[0032] The main raw materials and their specifications used in the embodiments and comparative examples of this invention are as follows: Water glass is industrial-grade sodium silicate solution produced by Shandong Youbang Silicon-based Materials Co., Ltd., with a modulus n (SiO2 / Na2O molar ratio) = 3.2 and a solid content of 36 wt% based on SiO2. It is diluted with deionized water to a working solution with a SiO2 mass concentration of 10%–12% before use. Hydrochloric acid is analytical grade hydrochloric acid produced by Sinopharm Chemical Reagent Co., Ltd., with a mass fraction of 36%–38%. It is diluted with deionized water to a working solution of 2 mol / L before use. Ammonia water is analytical grade ammonia water produced by Sinopharm Chemical Reagent Co., Ltd., with a mass fraction of 25%–28% (concentration approximately 13.4 mol / L). It is diluted to a working solution of 1 mol / L or used directly as the stock solution as needed. Zinc sulfate monohydrate (ZnSO4·H2O) and manganese sulfate monohydrate (MnSO4·H2O) are both analytical grade products produced by Tianjin Kemei Chemical Reagent Co., Ltd., with a purity ≥ 99.0%. Boric acid (H3BO3) is analytical grade, produced by Xilong Scientific Co., Ltd., with a purity ≥ 99.5%. Citric acid monohydrate (C6H8O7·H2O) is food grade, produced by Weifang Yingxuan Industrial Co., Ltd., with a purity ≥ 99.0%. Light-burned magnesium oxide (MgO) is industrial grade, produced by Liaoning Yingkou Dashiqiao Magnesium Oxide Plant, with an MgO content ≥ 85%, a citric acid activity value of 12–25 seconds (corresponding to light-burned active products with a calcination temperature of approximately 750–900℃), and a particle size of 200 mesh (d). 50 The surface of the sodium carboxymethyl cellulose (CMC-Na) is ≤ 45 μm. It is dried in an oven at 105℃ for 2 hours before use to remove surface adsorbed water. The industrial grade CMC-Na is from Shanghai Shanpu Chemical Co., Ltd., with a viscosity (2% aqueous solution, 25℃) of 800–1200 mPa·s. The anhydrous ethanol is analytical grade from Tianjin Fuyu Fine Chemical Co., Ltd. The conductivity of deionized water is ≤ 5 μS / cm.

[0033] The performance testing methods for the silicon-based trace element composite conditioner particles prepared in each embodiment and comparative example are as follows. Specific surface area and pore size distribution were determined using the nitrogen adsorption-desorption (BET) method. The instrument used was a Micromeritics ASAP 2460 fully automated specific surface area and porosity analyzer. Sample pretreatment conditions included vacuum degassing at 200℃ for 4 hours and an adsorption temperature of 77 K (liquid nitrogen temperature). Specific surface area was calculated using the BET multi-point method, and mesopore size distribution was calculated using the BJH method (Barrett-Joyner-Halenda model) based on the desorption isotherm branch. In the determination of nutrient content, the available SiO2 content was determined according to the silicomolybdenum blue colorimetric method in NY / T 2272—2012 "Determination of the content of effective components in soil conditioners"; the zinc and manganese contents were determined according to GB / T 14540—2003 using EDTA complexometric titration or atomic absorption spectrophotometry (AAS, Shimadzu AA-7000 model, Japan); the boron content was determined according to GB / T 14541—2017 using methanol distillation-curcumin colorimetric method; the magnesium oxide content was determined according to GB / T 1574—2007 using EDTA titration; and the sodium content was determined by flame atomic absorption spectrophotometry (AAS). The determination of cumulative nutrient release rate was carried out by modifying the column leaching test according to the European standard EN 13266:2001: 5.00 g of product particles (2-4 mm particle size) and 500 g of air-dried tobacco soil (taken from the main flue-cured tobacco producing area of ​​Meitan County, Zunyi City, Guizhou Province, with an initial pH of 4.82, organic matter content of 18.5 g / kg, and cation exchange capacity of 12.6 cmol / kg) were mixed evenly and placed in a 50 mm inner diameter polyvinyl chloride leaching column. The water content was maintained at 80% of the field capacity with deionized water and placed in a constant temperature incubator at 25℃. The column was leached with 200 mL of deionized water on days 3, 7, 14, 21, and 30, and the leachate was collected. The concentrations of available silicon, zinc, manganese, and boron in the leachate were measured, and the cumulative release rate at each time point was calculated as the percentage of the cumulative leaching amount to the total initial nutrients of the product. Soil pH was determined according to NY / T 1121.2—2006. A suspension was prepared with a water-to-soil ratio of 2.5:1 and measured using a Leici PHS-3C precision pH meter.Soil microbial community diversity analysis employed high-throughput 16S rRNA gene (bacteria) and ITS segment (fungi) amplicon sequencing: Soil samples from the 0–20 cm topsoil layer were collected, and total soil DNA was extracted using the MPBiomedicals FastDNA Spin Kit for Soil. The 16S rRNA V4 region was amplified using universal primers 515F / 806R, and the ITS1 segment was amplified using primers ITS1F / ITS2R. Paired-end sequencing was performed using the Illumina NovaSeq 6000 platform. Quality control, dechimeric analysis, ASV clustering, and species annotation were performed using the QIIME2 (version 2024.2) workflow (reference databases were SILVA 138.1 and UNITE 9.0). The Shannon diversity index and genus-level relative abundance were calculated. Among the agronomic traits and quality indicators of flue-cured tobacco, the opening degree (length-to-width ratio) of the upper tobacco leaves was determined according to YC / T 142—2010; the conventional chemical components (total sugar, reducing sugar, nicotine, total nitrogen, potassium, and chlorine) were determined according to the YC / T 159—2002 to YC / T 162—2002 series of standards; the sugar-to-nicotine ratio is the ratio of reducing sugar content to nicotine content; the sensory evaluation was conducted according to YC / T 530—2015, with a review panel composed of 7 qualified evaluators, using a 9-point scoring system to conduct blind evaluations of indicators such as sweetness, aroma, and raw, grassy, ​​and off-flavors.

[0034] In all the following examples and comparative examples, the field trials were conducted uniformly at the flue-cured tobacco planting base in Yongxing Town, Meitan County, Zunyi City, Guizhou Province (altitude approximately 860 m, average annual temperature 14.9℃, tested variety: Yunyan 87). The trials were conducted from March to September 2024. Each treatment was replicated three times, with each replicate covering an area of ​​0.5 mu (333 m²). 2 The samples were randomly assigned to blocks. The basic fertilization regimen, excluding the compound conditioner of this invention, was uniformly as follows: 50 kg / mu of flue-cured tobacco-specific compound fertilizer (N-P2O5-K2O = 10-12-22) was applied as base fertilizer, followed by 15 kg / mu of potassium nitrate 20 days after transplanting. No other silicon fertilizer or micronutrient / inorganic salt fertilizer was applied throughout the entire growth period. The control group (CK) received only the above basic fertilization regimen without any conditioner product. Soil sampling locations were uniformly set at the 0-20 cm tillage layer in the inter-row fertilization strip (within a horizontal distance of 10-15 cm from the tobacco plant rootstock) within each treatment plot to reflect the actual effect of the compound conditioner within the effective rhizosphere area. Since the base fertilizer is concentrated in the effective mixing zone 5-10 cm above the plow layer after rotary tillage, and the topdressing is concentrated in the inter-row furrow application zone, the effective concentration of the product in the fertilization zone is significantly higher than the assumed value of uniform distribution throughout the tillage layer. Therefore, the soil pH changes reported below reflect the local response of the rhizosphere soil in the fertilization zone, rather than the average value after uniform mixing throughout the field.

[0035] Example 1

[0036] This embodiment represents the central point of the preferred process conditions of the present invention. 1000 g of diluted water glass working solution (SiO2 concentration 11%, i.e., containing approximately 110 g of SiO2) was placed in a 5 L jacketed glass reactor. The anchor-type stirrer was turned on at a stirring speed of 280 rpm, and the jacket circulating cooling water maintained the solution temperature at 25°C. 2 mol / L hydrochloric acid working solution was slowly added dropwise to the water glass working solution using a peristaltic pump at a flow rate of 6 mL / min, with real-time monitoring using an online pH meter. When the pH of the solution dropped to 2.0, acid addition was stopped (approximately 590 mL of hydrochloric acid working solution was consumed, providing approximately 1.18 mol of HCl; of which approximately 1.14 mol was used to neutralize the alkali formed by approximately 0.57 mol of Na2O corresponding to 110 g of SiO2, and the remaining approximately 0.04 mol was used to make the system over-acidified to pH 2.0). Stirring continued for 40 minutes. The solution changed from milky white and translucent to slightly yellow and transparent, indicating complete hydrolysis and the formation of acidic silica sol. Transfer the acidic silica sol to a 5 L beaker, slowly add 300 mL of anhydrous ethanol (approximately 0.3:1 volume ratio to silica sol), stir magnetically for 5 minutes, let stand for 15 minutes, and then filter under reduced pressure. Wash the filter cake three times with 800 mL of deionized water until no white precipitate is detected by AgNO3 solution and the conductivity drops to 38 μS / cm. Redisperse the washed low-sodium silica gel primary in 500 mL of deionized water and stir until homogeneous.

[0037] Separately, dissolve 118 g of citric acid monohydrate in 300 mL of deionized water (40℃ water bath), stirring until completely dissolved. Then, add 42 g of zinc sulfate monohydrate, 30 g of manganese sulfate monohydrate, and 20 g of boric acid sequentially, stirring at 45℃ and 200 rpm for 30 minutes until completely dissolved. At this point, citric acid (0.562 mol) and Zn... 2+ (0.234 mol) and Mn 2+ The ratio of the total molar amount of (0.177 mol) to (0.411 mol) is 1.37:1, which is within the preferred range of 1.2:1 to 1.5:1, and the solution is transparent and free of precipitate.

[0038] The aforementioned low-sodium silicate gel suspension was transferred to a 5 L jacketed reactor. The mixture was stirred at 220 rpm, and the jacketed circulating hot water was heated to 60 °C at a rate of 1.5 °C / min and stabilized. The trace element chelation mother liquor was pumped in at 25 mL / min and stirred for 10 minutes. Subsequently, 38 g of lightly calcined magnesium oxide powder (34.5% of the initial 110 g SiO2 mass) was added in four batches, approximately 9.5 g per batch, with a 5-minute interval between each addition, and stirred until homogeneous after each addition. As MgO dissolved in batches and the system's buffer acidity was gradually consumed, the pH of the system slowly increased from approximately 2.5 to approximately 4.7. The system was then precisely fine-tuned with 1 mol / L ammonia water to adjust the pH to 5.3 (consuming approximately 85 mL of ammonia water, providing approximately 0.085 mol alkali equivalent). The reaction was continuously stirred at 60℃ and pH 5.3 for 2.5 hours. It was observed that the torque of the stirring paddle increased by about 42% compared with the initial value. The liquid did not flow after the reactor was inverted for 5 seconds, indicating that gelation was complete.

[0039] Stop stirring and allow the gel to age at 60°C for 15 hours in the reactor. After aging, take a sample and determine the specific surface area using the BET method; it is 236 m². 2 / g, the BJH pore size distribution peak is 5.7 nm, and the half-peak width is 2.4 nm. The aged gel was removed and broken into pieces of approximately 5–10 mm using a scraper, spread on a stainless steel tray (layer thickness approximately 15 mm), and dried in a 60℃ forced-air drying oven for 7 hours, then heated to 105℃ and dried for another 5 hours until constant weight. The dried product was a pale yellow porous block, coarsely crushed to <5 mm using a jaw crusher, then ball-milled and passed through a 100-mesh sieve to obtain the composite conditioner powder. 1000 g of the powder was placed in a V-type mixer, and 20 g of CMC-Na powder (2% of the powder mass) was added. The mixture was mixed for 10 minutes to ensure uniform dispersion of CMC-Na. The premixed powder was transferred to a disc granulator (800 mm diameter, 47° inclination, 20 rpm), and sprayed with deionized water through a two-fluid nozzle at a spray rate of 8 mL / min, with a total water addition of approximately 220 mL (liquid-to-solid ratio 0.22:1). After granulation, 2–4 mm particles were sieved and dried in a fluidized bed dryer at 80°C for 1.5 hours until the moisture content reached 4.2%, yielding the final product.

[0040] Field application plan: 8 days before transplanting flue-cured tobacco, spread the granules at 50 kg / mu on the surface and then rotary till them into the 0-20cm tillage layer; 30 days after transplanting (during the seedling stage), apply 18 kg / mu in furrows (8 cm deep) between the tobacco rows and backfill with soil.

[0041] Example 2

[0042] This embodiment represents a lower limit parameter combination scheme within the scope of the claims. Take 1000 g of water glass diluted working solution (SiO2 concentration 10%, containing approximately 100 g of SiO2). Acid-catalyzed hydrolysis stage: Slowly add 2 mol / L hydrochloric acid working solution dropwise at a flow rate of 6 mL / min using a peristaltic pump until the system pH drops to 2.5, then stop adding acid (approximately 530 mL of hydrochloric acid working solution is consumed, providing approximately 1.06 mol HCl, of which approximately 1.04 mol is used to neutralize approximately 0.52 mol Na2O corresponding to 100 g SiO2). Continue stirring for 45 minutes to complete the hydrolysis. The sodium removal process is the same as in Example 1.

[0043] Preparation of trace element chelate solution: Take 88 g (0.419 mol) of citric acid monohydrate and 35 g (Zn) of zinc sulfate monohydrate. 2+ 0.195 mol), 25 g of manganese sulfate monohydrate (Mn) 2+ The operating conditions were the same as in Example 1, using 0.148 mol of citric acid and 15 g of boric acid. The ratio of citric acid to the total molar amount of metal ions (0.343 mol) was 1.22:1.

[0044] Alkali-catalyzed polycondensation-co-deposition stage: The reaction temperature was 55℃. The total amount of lightly calcined magnesium oxide added was 25 g (25.0% of the initial SiO2 mass of 100 g), added in 3 batches, each batch approximately 8.3 g. After the MgO was added in batches, the pH of the system gradually increased to approximately 4.3. The pH of the system was precisely adjusted to 5.0 with 1 mol / L ammonia water (consuming approximately 120 mL of ammonia water). The mixture was stirred continuously for 3 hours at 55℃ and pH 5.0 until gelation was complete. The aging condition was 18 hours of standing at 55℃. The BET specific surface area was 198 m². 2 / g, BJH pore size peak 7.1 nm, half peak width 2.8 nm. Drying and granulation operations were the same as in Example 1, CMC-Na amount was 1% of dry powder mass, and the final product moisture content was 4.5%.

[0045] Field application plan: Apply 40 kg / mu as basal fertilizer 10 days before transplanting, and apply 15 kg / mu as top dressing during the seedling stage.

[0046] Example 3

[0047] This embodiment represents a high-limit parameter combination scheme within the scope of the claims. Take 1000 g of water glass diluted working solution (SiO2 concentration 12%, containing approximately 120 g of SiO2). Acid-catalyzed hydrolysis stage: Slowly add 2 mol / L hydrochloric acid working solution until the system pH reaches 1.5, then stop adding acid (approximately 660 mL of hydrochloric acid working solution is consumed, providing approximately 1.32 mol of HCl, of which approximately 1.25 mol is used to neutralize approximately 0.625 mol of Na2O corresponding to 120 g of SiO2). Stir for 30 minutes to complete the hydrolysis. The amount of anhydrous ethanol used in the sodium removal treatment is 500 mL (volume ratio approximately 0.5:1).

[0048] Trace element chelate solution: 152 g (0.723 mol) citric acid monohydrate, 50 g (Zn) zinc sulfate monohydrate 2+ 0.279 mol), 35 g of manganese sulfate monohydrate (Mn) 2+ 0.207 mol), boric acid 25 g. The ratio of citric acid to the total molar amount of metal ions (0.486 mol) is 1.49:1.

[0049] Alkali-catalyzed polycondensation-co-deposition stage: The reaction temperature was 65℃, and the total amount of lightly calcined magnesium oxide (MgO) added was 50 g (41.7% of the initial SiO2 mass of 120 g), added in 4 batches. After the MgO was added in batches, the pH of the system gradually increased to approximately 5.1. The pH of the system was precisely adjusted to 5.5 with 1 mol / L ammonia water (consuming approximately 55 mL of ammonia water), and gelation was completed by stirring for 2 hours at 65℃ and pH 5.5. The aging condition was 12 hours of standing at 65℃. The BET specific surface area was 268 m². 2 / g, BJH pore size peak 4.4 nm, half peak width 2.1 nm. Drying and granulation were the same as in Example 1, CMC-Na was used at 3% of the dry powder mass, and the final product moisture content was 3.8%.

[0050] Field application: Apply 60 kg / mu as a base 7 days before transplanting, and apply 20 kg / mu as a top dressing during the seedling stage.

[0051] Example 4

[0052] This embodiment adjusts the amount of lightly calcined magnesium oxide (MgO) to near the lower limit and appropriately lowers the polycondensation temperature based on Example 1 to investigate the effect of MgO addition on pH buffering performance. The preparation of the silicon source working solution, acid-catalyzed hydrolysis (final pH 2.0, consuming approximately 590 mL of hydrochloric acid working solution), sodium removal treatment, and trace element chelation solution are all the same as in Example 1. Alkali-catalyzed polycondensation-co-deposition stage: reaction temperature 57℃, total added amount of lightly calcined magnesium oxide 28 g (25.5% of the initial SiO2 mass of 110 g), added in 3 batches. After the batch addition of MgO, the pH of the system gradually rises to approximately 4.0. The pH of the system is adjusted to 5.2 with 1 mol / L ammonia (consuming approximately 165 mL of ammonia), and gelation is completed by stirring for 2.5 hours at 57℃ and pH 5.2. Aging conditions are 16 hours of standing at 57℃. BET specific surface area is 215 m² / g, BJH pore size peak is 6.2 nm, and half-maximum width at half-maximum is 2.6 nm. Drying and granulation were performed in the same manner as in Example 1, with CMC-Na dosage at 2%.

[0053] Field application is the same as in Example 1.

[0054] Example 5

[0055] This embodiment, based on Example 1, adjusts the condensation pH value to the upper boundary of the preferred range and increases the MgO dosage to near the upper limit, investigating the synergistic effect of condensation pH and MgO dosage on product performance. The silicon source working solution (SiO2 concentration 11%, 110 g SiO2), acid-catalyzed hydrolysis (final pH 1.8, consuming approximately 600 mL of hydrochloric acid working solution), and sodium removal treatment are the same as in Example 1. The trace element chelating solution is the same as in Example 1. Alkali-catalyzed condensation-co-deposition stage: reaction temperature 63℃, total addition of lightly calcined magnesium oxide 46 g (accounting for 41.8% of the SiO2 mass), added in 4 batches. After the batch addition of MgO, the system pH gradually rises to approximately 5.2. The system pH is precisely adjusted to 5.5 with 1 mol / L ammonia water (consuming approximately 45 mL of ammonia water), and gelation is completed by stirring for 2 hours at 63℃ and pH 5.5. The aging condition is standing at 63℃ for 13 hours. BET specific surface area 252 m² 2 / g, BJH pore size peak 4.8 nm, half-peak width 2.2 nm. Drying and granulation were the same as in Example 1, with CMC-Na dosage 2.5%.

[0056] Field application is the same as in Example 1.

[0057] Example 6

[0058] This embodiment, based on Example 1, adjusts the endpoint pH of acid-catalyzed hydrolysis to a slightly higher value in the middle range (pH 2.3), and adjusts the SiO2 concentration of the working solution to 10.5% to verify the robustness of different combinations of parameters within the scope of the claims. The silicon source working solution (SiO2 concentration 10.5%, approximately 105 g SiO2), with an acid-catalyzed hydrolysis endpoint pH of 2.3 (consuming approximately 555 mL of hydrochloric acid working solution), is stirred for 35 minutes to complete the hydrolysis. The sodium removal treatment is the same as in Example 1 (ethanol volume 350 mL, volume ratio approximately 0.35:1). The trace element chelating solution consists of 97 g (0.462 mol) citric acid monohydrate and 38 g (Zn) zinc sulfate monohydrate. 2+ 0.212 mol), 28 g of manganese sulfate monohydrate (Mn) 2+ The total molar ratio of citric acid to metal ions (0.378 mol) was 1.22:1. Alkali-catalyzed polycondensation-co-deposition stage: reaction temperature 58℃, total added amount of lightly calcined magnesium oxide 35 g (33.3% of SiO2 mass), added in 3 batches. After the batch addition of MgO, the pH of the system gradually increased to approximately 4.6. The pH of the system was adjusted to 5.1 with 1 mol / L ammonia water (consuming approximately 90 mL of ammonia water), and gelation was completed by stirring for 2.5 hours at 58℃ and pH 5.1. Aging conditions: standing at 58℃ for 15 hours. BET specific surface area 222 m². 2 / g, BJH pore size peak 6.0 nm, half-maximum width at half-maximum 2.5 nm. Drying and granulation were the same as in Example 1, with CMC-Na dosage of 1.5%.

[0059] Field application is the same as in Example 1.

[0060] Comparative Example 1

[0061] This comparative example uses a conventional physical mixing method, that is, without combining the components through a sol-gel chemical reaction, but by preparing granular fertilizer by simply mixing equal amounts of nutrients separately. The aim is to verify the core inventive point of this invention, namely the necessity of the molecular-level composite structure constructed by the sol-gel chemical process relative to physical mixing. The raw materials were prepared according to the same nutrient content principle as in Example 1: 306 g of industrial-grade water glass stock solution (same as in Example 1, SiO2 36%, n = 3.2) (equivalent to approximately 110 g of SiO2) was taken and dried in an 80℃ forced-air drying oven to obtain approximately 153 g of water glass powder (containing approximately 110 g of SiO2 and approximately 34.4 g of Na2O). This powder was ball-milled until it passed through a 100-mesh sieve. Separately, 42 g of zinc sulfate monohydrate, 30 g of manganese sulfate monohydrate, 20 g of boric acid, and 38 g of lightly calcined magnesium oxide were weighed. The above powder was dry-mixed with 343 g of kaolin powder (passed through a 325-mesh sieve) in a V-type mixer for 20 minutes to ensure uniform dispersion of the components, resulting in a total dry powder of approximately 626 g. 12 g of CMC-Na dry powder (2% of the dry powder mass) was premixed with the mixed powder, and then wet-granulated in a disc granulator using deionized water as a wetting agent (operating conditions as in Example 1). Particles of 2–4 mm were sieved and dried at 80°C to a moisture content of 4.8%, yielding a final product of approximately 638 g. This product lacks a mesoporous gel framework structure; the nutrient components are only interlocked as micron-sized particles. The theoretical SiO2 content of this product was calculated to be 110 / 638 = 17.2% (due to the water-soluble nature of sodium silicate, the effective SiO2 content is approximately 17.0%), and the Na content was 34.4 × 46 / 62 / 638 = 4.00%. The field application scheme was the same as in Example 1.

[0062] Comparative Example 2

[0063] This comparative example omits the citric acid chelation step, introducing zinc, manganese, and boron directly into the alkali-catalyzed polycondensation stage in their free inorganic salt state. This aims to verify the necessity of chelation protection for product structural uniformity and sustained-release performance. The preparation of the silicon source working solution and the acid-catalyzed hydrolysis (consuming approximately 590 mL of hydrochloric acid working solution) and desodium treatment were performed exactly as in Example 1. Instead of preparing a chelation solution, 42 g of zinc sulfate monohydrate, 30 g of manganese sulfate monohydrate, and 20 g of boric acid were directly dissolved in 300 mL of deionized water (without adding citric acid). Alkali-catalyzed polycondensation-co-deposition stage: The above inorganic salt solution and 38 g of lightly calcined magnesium oxide were added to the low-sodium silicate gel suspension as described in Example 1. Since the system lacks a citric acid buffer, the addition of MgO caused a more rapid pH increase. The pH was adjusted to 5.3 with 1 mol / L ammonia (consuming approximately 50 mL of ammonia), and the mixture was stirred at 60°C. After the overall pH of the system rises to approximately 5.0 or higher, the pH of the local micro-regions on the dissolved surface of MgO particles instantaneously reaches 7-8 or higher (far higher than the homogeneous pH of the system), and the free Zn... 2+In these locally high pH micro-regions, fine Zn(OH)2 precipitates are formed first (the critical pH at which Zn(OH)2 begins to precipitate is approximately 6.0), and the solution becomes white and turbid, which gradually worsens. Simultaneously, free metal ions are largely deprotonated by silanol groups (≡Si-O) on the surface of the silica gel without chelation protection. - ) through ion exchange adsorption (≡Si-O) - + M 2+ → ≡Si-OM + This resulted in the accumulation of metal ions on the surface layer of the gel, while the internal pores were scarce, leading to a severely uneven distribution. During stirring, the white precipitate continued to increase and partially blocked the stirring paddle. After struggling to continue stirring for 2.5 hours, although the system gelled, the white, opaque precipitate clumps within the gel were visibly unevenly distributed. The aging, drying, and granulation procedures were the same as in Example 1. The BET specific surface area was 178 m². 2 / g, the pore size distribution exhibits a bimodal characteristic (peaks at 3.2 nm and 11.5 nm, respectively), indicating that precipitate agglomerates and a non-uniform adsorption layer block some mesopores and cause skeletal defects in other areas, resulting in macropores. Field application is the same as in Example 1.

[0064] Comparative Example 3

[0065] This comparative example adjusts the pH value of the alkali-catalyzed polycondensation stage to outside the scope of the claims (pH 6.5) to verify the criticality of the 5.0–5.5 pH window for mesoporous structure control during polycondensation. The preparation of the silicon source working solution, acid-catalyzed hydrolysis (consuming approximately 590 mL of hydrochloric acid working solution), sodium removal treatment, and trace element chelation solution were exactly the same as in Example 1. Alkali-catalyzed polycondensation-co-deposition stage: reaction temperature 60°C, 38 g of lightly calcined magnesium oxide was added in four batches, and the pH of the system was adjusted to 6.5 with 1 mol / L ammonia (after the addition of MgO, the system pH had already risen to approximately 4.7; subsequently, approximately 240 mL of ammonia was consumed to further adjust the pH from 4.7 to 6.5). Within approximately 15 minutes of reaching pH 6.0, rapid thickening and gelation of the system were observed (much faster than the 2.5 hours in Example 1), and a small number of pale white, translucent precipitate spots appeared in the gel. Aging conditions: 60°C for 15 hours. The BET specific surface area is only 86 m² / g, and the BJH pore size peak is 2.8 nm, indicating that the excessively rapid polymerization rate leads to over-densification of the gel skeleton and the closure of a large number of mesopores. Drying and granulation procedures are the same as in Example 1. Field application is the same as in Example 1.

[0066] Comparative Example 4

[0067] This comparative example does not include any lightly calcined magnesium oxide (MgO) component, and the remaining process operations are exactly the same as in Example 1. The aim is to verify the indispensability of MgO component in the product's pH buffering function and soil microecological regulation effect. Specifically, in the alkali-catalyzed polycondensation stage, only ammonia water is used to adjust the pH to 5.3. Since no MgO is added, all the acidity in the system (approximately 1.15 mol equivalents of citric acid buffering acidity + approximately 0.5 mol equivalents of silanol buffering acidity + approximately 0.02 mol equivalents of residual free acidity, totaling approximately 1.67 mol) must be neutralized entirely by the alkali equivalent provided by ammonia water. Considering that using 1 mol / L dilute ammonia water would cause excessive expansion of the system volume (approximately 1670 mL), severely diluting the reactant concentration and affecting the gelation quality, this comparative example uses 25% concentrated ammonia water (approximately 13.4 mol / L) added dropwise, consuming approximately 125 mL of concentrated ammonia water (providing approximately 1.68 mol alkali equivalents). Compared to Example 1, where MgO accounted for the majority of alkalinity and ammonia was only used for minor adjustments, the concentrated addition of a large amount of ammonia in this comparative example made it difficult to completely avoid localized over-alkalinity, resulting in a decrease in the uniformity of the gelation process. The aging, drying, and granulation operations were the same as in Example 1. The BET specific surface area was 241 m². 2 / g, BJH pore size peak 5.6 nm, mesoporous structure similar to Example 1 (because the main body of the gel skeleton is still a silica network). Field application is the same as in Example 1.

[0068] The physicochemical properties and cumulative nutrient release rate of the soil column leaching over 30 days for the products prepared in each example and comparative example are summarized in Table 1. It should be noted that the "effective SiO2 content" in the table is the percentage of extractable SiO2 relative to the total mass of the product, determined under specified conditions using citric acid solution as the extractant according to the NY / T 2272—2012 standard method, and not the total chemical content of SiO2 in the product. For the products in the examples, the total SiO2 content (approximately 30%–33%) is significantly higher than the effective SiO2 content (approximately 17%–20%). The difference is due to the gel-structured SiO2 that has not yet dissolved under standard extraction conditions, which directly reflects the slow-release structure. For the physically mixed product of Comparative Example 1, since sodium silicate is a water-soluble silicon source, its effective SiO2 content is basically consistent with the theoretical total SiO2 content.

[0069] Table 1. Physicochemical properties and cumulative nutrient release rates of the products in each embodiment and comparative example.

[0070] The field soil properties and flue-cured tobacco quality index data after application of each embodiment and comparative example are summarized in Table 2. The soil data were collected from the 0-20 cm rhizosphere soil samples in the inter-row fertilization strip (10-15 cm horizontal distance from the rootstock of the tobacco plant) in each treatment plot 90 days after transplanting (mid-maturity stage). The flue-cured tobacco quality data were collected from samples of the upper tobacco leaves (B2F leaf position) after curing.

[0071] Table 2. Rhizosphere soil properties and flue-cured tobacco quality indicators in the field fertilization zone.

[0072] The following is a comprehensive analysis of the data in Tables 1 and 2 above.

[0073] First, the data trends across the various examples show a clear negative correlation between the mesoporous structure parameters of the product and the nutrient slow-release rate. Example 3 (condensation pH 5.5, temperature 65℃, MgO content 41.7%) represents the upper limit of process parameters, exhibiting the highest specific surface area (268 m²). 2 / g) with the smallest mesopore size (4.4 nm), corresponding to the lowest cumulative SiO2 release rate over 30 days (51.6%); Example 2 (condensation pH 5.0, temperature 55℃, MgO content 25.0%) represents the lower limit process parameters, with the lowest specific surface area (198 m²). 2 The mesoporous pores had the largest diameter (7.1 nm), corresponding to the highest cumulative SiO2 release rate over 30 days (64.8%). This trend perfectly aligns with Knudsen diffusion theory of molecular mass transfer in mesoporous materials: as the pore size decreases, the frequency of collisions between diffusing molecules and the pore walls increases, and the effective diffusion coefficient decreases with decreasing pore size. Therefore, the rate of nutrient release from the gel skeleton into the soil solution decreases with decreasing mesoporous pore size. The release rate data for Example 1 (central process conditions) (SiO2 57.3%, Zn 41.5%, Mn 43.8%, B 52.1%) fall between those of Examples 2 and 3, and generally maintain the same trend as the data for Examples 4, 5, and 6 under different combinations of parameters. This demonstrates the robustness of the process window of this invention; that is, by adjusting the specific values ​​of each process parameter within the parameter range defined in the claims, although the product performance may fluctuate reasonably, a SiO2 release rate of 55%–65% and a trace element release rate of 36%–49% can be achieved. The release rate mentioned above is much lower than >86% of Comparative Example 1 (physically mixed product) and also lower than 65% to 72% of Comparative Example 2 (without chelation protection), but significantly higher than 12% to 19% of Comparative Example 3 (overly dense skeleton). This indicates that the condensation pH window of 5.0 to 5.5 set by the present invention precisely controls the nutrient release rate within a reasonable range that matches the demand rhythm of flue-cured tobacco throughout its entire growth period.

[0074] Further analysis was conducted at the chemical mechanism level of mesoporous structure formation. The mesopore sizes of Examples 1–6 were all distributed in the range of 4.4–7.1 nm, and the full width at half maximum (FWHM) was ≤ 2.8 nm, indicating a narrow and uniform pore size distribution. This is attributed to the characteristic microstructure of the branched gel framework formed under pH conditions of 5.0–5.5 during the alkaline-catalyzed polycondensation stage: within this pH window, OH... - The kinetic rate constant of the catalytic Si-O-Si condensation reaction is at a moderate level (relative to the extremely slow reaction in the acid-catalyzed region and the extremely fast reaction in the strong-base-catalyzed region). Orthosilicic acid monomers preferentially condense to the ends or branch points of existing oligomeric segments (Reaction-Limited Cluster Aggregation, RLCA), forming a branched three-dimensional network with a high fractal dimension (df ≈ 2.0–2.1). The spacing between the network framework segments defines the mesopore size, and its uniformity stems from the uniformity of growth rates across the framework under the RLCA mechanism. In contrast, in Comparative Example 3 (pH 6.5), excessively high OH... - Concentration leads to a sharp increase in the polymerization rate (diffusion-limited cluster aggregation, DLCA) and the orthosilicic acid monomers are consumed by rapid surface reactions before they can diffuse into the deep part of the framework. This results in excessive densification of the framework surface and the leaving of a small number of large-scale defect cavities inside. This is the fundamental reason why the specific surface area of ​​Comparative Example 3 drops sharply to 86 m² / g and the pore size narrows to 2.8 nm (a large number of mesopores are closed, leaving only extremely small micropores and a small number of defect macropores that can be detected by the BET method). The SiO2 release rate of Comparative Example 3 in 30 days was only 18.5%, which means that even considering the cumulative effect of continuous acid erosion in the soil during the later stages, the total release of available silicon during the 120-day growth period is still far from meeting the silicon nutrient requirements of flue-cured tobacco from the vigorous growth stage to maturity. Field data shows that the upper leaf opening degree of Comparative Example 3 increased by only 3.0% (significantly lower than 10.8% in Example 1), the nicotine content was as high as 3.35%, and the sugar-alkali ratio was only 5.12, all of which confirm that the severe nutrient supply shortage led to an imbalance in carbon and nitrogen metabolism.

[0075] Comparative Example 2 (without citric acid chelation protection) further reveals the crucial role of the chelated state in the product's structural integrity. This is due to the free Zn... 2+ and Mn 2+When the pH of the system rises above 5.0, hydroxide precipitates are generated in localized high-pH micro-regions on the dissolved surface of MgO particles. Simultaneously, non-uniform ion exchange adsorption occurs on the gel surface. These precipitate agglomerates and adsorption-enriched layers are randomly incorporated into the framework during gelation, resulting in two consequences: First, the large volume of the precipitate agglomerates (micrometer-scale) blocks the mesoporous channels in their adjacent areas, hindering nutrient release in these regions (manifested as a low-pore-size peak at 3.2 nm). Second, the presence of precipitate agglomerates disrupts the continuity of the silica gel network in these regions, leading to structural defects and macropores in the framework (manifested as a high-pore-size peak at 11.5 nm). Nutrients in these macroporous regions are released too quickly, losing their slow-release function. The net effect of the bimodal pore size distribution is that, although the cumulative release rates of Zn and Mn over 30 days in Comparative Example 2 (67.4% and 69.2%) were lower than those in the physical mixing of Comparative Example 1 (86.3% and 88.7%), they were still much higher than those in Example 1 (41.5% and 43.8%), indicating that some nutrients leaked out uncontrollably and rapidly through the macropores of the skeletal defects. Field results showed that the improvement in soil microbial community (Bacillus +8.3%, Fusarium -8.7%) and tobacco quality indicators (sugar-alkali ratio 5.42, sweetness score 5.8) in Comparative Example 2 were significantly lower than any of Examples 1-6, which, conversely, confirms the irreplaceable role of citric acid chelate in maintaining product structural uniformity and slow-release function.

[0076] The data from Comparative Example 1 (physically mixed product) most intuitively demonstrates the significant advantages of the sol-gel chemical process of this invention compared to simple physical mixing. The physically mixed product lacks a mesoporous gel framework structure; each nutrient component is interlocked as micron-sized particles, allowing for direct dissolution or ion exchange upon exposure to soil water. Therefore, the cumulative release rate over 30 days exceeds 86%, with SiO2 release reaching as high as 92.4%. This means that most nutrients have entered the soil solution within less than a week of fertilization. In acidic tobacco-growing soils, the direct consequence of such a large amount of rapidly released nutrients is that the released available silicon quickly reacts with active Al in the soil. 3+ and Fe 3+ The reaction forms insoluble aluminosilicate and ferrosilicate precipitates, which are then fixed; the released free Zn 2+ and Mn 2+It is also easily adsorbed and fixed by soil iron and manganese oxides or precipitates with phosphate. Therefore, although the initial total nutrient content of Comparative Example 1 is comparable to that of Example 1, the field availability of Comparative Example 1 is far less than that of Example 1. More notably, the Na content in the product of Comparative Example 1 is as high as 4.00 wt% (derived from sodium silicate used as a silicon source without desodiumning), while the Na content in Examples 1-6 is controlled between 0.09 and 0.15 wt%. The high sodium content directly results in a very limited increase in the pH of the rhizosphere soil in the fertilization zone of Comparative Example 1 (only +0.08), because Na + Although H is not directly produced in the soil + However, the resulting soil dispersion reduces aggregate stability and weakens the soil's natural buffering capacity. The improvement in microbial community (Bacillus only +2.8%, Fusarium only -3.1%) and tobacco quality indicators (sugar-alkali ratio 4.86, sweet aroma score 5.5, raw and unpleasant aroma score 3.8) in Comparative Example 1 were very similar to the control (CK), fully demonstrating the limitations of the physical blending technique.

[0077] The data from Comparative Example 4 (without MgO) precisely reveals the pH buffering function of the lightly calcined magnesium oxide component in the technical solution of this invention. Because Comparative Example 4 retains the complete sol-gel process and citric acid chelation step, its mesoporous structure (specific surface area 241 m²) is... 2 The MgO content (5.6 nm pore size) and nutrient slow-release performance (55.8% SiO2 release rate and 40.2% Zn after 30 days) were basically the same as in Example 1, proving that the MgO component is not indispensable for the formation of the gel framework (the silica gel network itself can self-assemble into a mesoporous structure). However, the pH increase of the rhizosphere soil in the fertilization zone of Comparative Example 4 was only +0.11 units (4.82→4.93), far lower than the +0.38 units (4.82→5.20) in Example 1. The chemical nature of this difference lies in the fact that the reaction that relies solely on the dissolution and consumption of H⁺ by the silica gel framework (≡Si-O-Si≡ + H₂O + H⁺) is significantly different. + The alkalinity release rate provided by H4SiO4 is limited, insufficient to raise the soil pH of the fertilized zone to above 5.0 within a growing season. Furthermore, the continuous hydration reaction of the MgO / Mg(OH)2 component in Example 1 under acidic conditions (MgO + H2O → Mg(OH)2; Mg(OH)2 + 2H2O) is insufficient. + → Mg 2+ + 2H2O) provides an additional and more robust source of alkalinity, with two alkalinity release mechanisms (silicon etching consumes H+). + +MgO hydration releases OH -To achieve an effective pH increase of 0.2–0.5 units within the fertilization zone, synergy is necessary. Furthermore, Comparative Example 4, due to the use of a large amount of concentrated ammonia to adjust the pH in a single step during preparation, exhibited slightly less uniform gelation compared to the gradual MgO release method in Example 1. However, since the ammonia evaporates and does not remain in the product, its impact on the mesoporous structure is limited. While the microbial community recovery effect of Comparative Example 4 (Bacillus +5.1%, Fusarium -5.7%) was better than the blank control and Comparative Example 1, it was still significantly inferior to all examples. This aligns with the widely accepted understanding in soil microbiology that "bacterial community abundance is positively correlated with increasing pH," meaning that the rhizosphere pH in the fertilization zone was not sufficiently raised to above 5.0, thus limiting the response of the microbial community. Although the tobacco quality indicators of Comparative Example 4 (sugar-alkali ratio 5.58, sweetness score 5.9) were better than Comparative Examples 1–3 due to the slow-release supply of available silicon and trace elements, the effect was still limited by the MgO release. 2+ The lack of supply led to limited chlorophyll synthesis and a decrease in photosynthetic carbon fixation capacity. As a result, the sugar-to-alkali ratio and sweet aroma score were still lower than those of Example 1 (sugar-to-alkali ratio 6.51, sweet aroma score 6.5 points), while the green and off-flavor score (3.2 points) was higher than that of Example 1 (2.5 points). This further proves the indispensability of MgO components in perfecting the carbon and nitrogen metabolism balance of flue-cured tobacco.

[0078] Comparing Example 4 (MgO content 25.5%) with Example 5 (MgO content 41.8%), it can be seen that the pH increase in the rhizosphere soil of the fertilization zone in Example 4 was +0.24, while that in Example 5 was +0.45, showing a positive correlation between the increase in MgO content and the increase in pH. However, the 30-day SiO2 release rate of Example 5 (53.4%) was slightly lower than that of Example 4 (60.2%). This is because more Mg(OH)2 nanosheets participated in the co-condensation of the framework, forming a denser magnesium-silicon composite node, which enhanced the resistance of the gel network to acid corrosion and slightly reduced the corrosion rate. However, the difference in release rates between the two is within an acceptable range (both within the target range of 53% to 65%), and the higher pH buffering capacity of Example 5 resulted in more significant improvement in the microecology and quality (Bacillus +22.8%, sugar-alkali ratio 6.65), indicating that within the MgO range of 25% to 42% as defined in the claims, the higher MgO dosage is superior in overall technical effect but does not constitute a disruption to the sustained-release function.

[0079] In summary, the experimental data in Tables 1 and 2 systematically demonstrate the following conclusions from five dimensions: product structure, nutrient release kinetics, soil chemistry, soil microbiology, and flue-cured tobacco quality: (1) The sol-gel chemical process of this invention has an essential slow-release advantage over physical mixing (Comparative Example 1), the fundamental reason being the dual binding mechanism of physical encapsulation and chemical weak bonding of chelated nutrients by the mesoporous gel framework; (2) Citric acid chelation protection is indispensable for maintaining the uniformity of the product's mesoporous structure and the uniformity of nutrient distribution (Comparative Example 2), the chemical principle of which is that the chelating complex maintains the dissolved state of metal ions during the alkaline catalytic condensation stage, avoids hydroxide precipitation in local high pH micro-regions, and prevents non-uniform surface adsorption from clogging the pores; (3) The condensation pH window of 5.0 to 5.5 is the control window for mesoporous pore size (4 to 8). The core parameters of the nutrient release rate (nm) and the nutrient release rate (Comparative Example 3) are as follows: below this range, the skeleton is too loose and loses its slow-release function; above this range, the skeleton is too dense and leads to nutrient blockage. (4) The lightly burned magnesium oxide component is a necessary component for effectively improving the pH of the rhizosphere soil and improving the microecology in the fertilization zone (Comparative Example 4). Its synergistic effect of hydration alkali release and gel dissolution acid consumption cannot be replaced by a single mechanism. It should be noted that the above-mentioned transformation of the soil microbial community from "fungus-dominant" to "bacterial-dominant" is essentially a secondary effect caused by pH increase, which conforms to the general response law of pH-microbial community structure in soil microbiology. The unique contribution of this invention is that it achieves a slow, continuous, and gentle increase in pH through the slow-release mechanism of the gel skeleton, avoiding the disturbance of soil microecology caused by the violent pH fluctuations caused by conventional quick-acting alkaline materials such as lime. Through the synergistic effect of the above four core technical features, this invention achieves the systematic technical goal of "slow-release nutrient supply - pH buffering - microecological improvement - tobacco quality improvement" in a unified chemical process.

[0080] The above description is only a preferred embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural or procedural transformations made based on the content of the present invention specification, or direct or indirect applications in other related technical fields, are similarly included within the patent protection scope of the present invention.

Claims

1. A method for regulating the microecological environment of tobacco-growing soil using silicon fertilizer and trace elements, characterized in that, Includes the following steps: S1. Provide an aqueous solution of silicon source, add an acidic catalyst under stirring conditions to carry out an acid-catalyzed hydrolysis reaction, and then remove the by-product salts generated by hydrolysis to obtain a low-sodium silicate primary suspension. S2. The zinc source, manganese source and boron source are mixed with the chelating agent in an aqueous solvent to prepare a trace element chelating solution. S3. Under heating and stirring conditions, the trace element chelate solution is added to the low sodium silicate gel primary suspension and mixed evenly. Lightly calcined magnesium oxide powder is added in batches. Then, an alkaline regulator is added to adjust the pH value of the system to carry out an alkaline catalytic condensation reaction, so that the chelated zinc and manganese, the molecular boric acid and the lightly calcined magnesium oxide are co-deposited in situ and embedded into the three-dimensional network framework of the silica mesoporous gel generated with the reaction, and a gelation transformation occurs to obtain a gel body. S4. The gel is subjected to aging treatment, drying and granulation in sequence to obtain silicon-based trace element composite conditioner particles. S5. During the tobacco planting stage, the silicon-based micronutrient compound conditioner particles are applied as base fertilizer and / or top dressing to acidic tobacco-growing soil. Through the gradual dissolution of the silicon gel skeleton under acidic conditions, the effective silicon, chelated zinc and manganese, and molecular boron are released simultaneously and slowly, thereby regulating the pH and microecological environment of the tobacco-growing soil.

2. The method as described in claim 1, characterized in that, In step S1, the silicon source aqueous solution is a water glass dilution solution with a silicon dioxide mass concentration of 10% to 12%; the acidic catalyst is hydrochloric acid, which is slowly added to lower the pH value of the system to 1.5 to 2.5; the process of removing by-product salts generated by hydrolysis includes: adding anhydrous ethanol to the hydrolyzed system to promote the appropriate aggregation of the primary silica gel, retaining the solid after solid-liquid separation, and washing the solid with deionized water until the washing liquid is free of chloride ions.

3. The method as described in claim 1, characterized in that, In step S2, the chelating agent is citric acid, the zinc source is zinc sulfate, the manganese source is manganese sulfate, and the boron source is boric acid; the molar ratio of citric acid to the total molar amount of zinc ions and manganese ions is controlled to be 1.2:1 to 1.5:

1.

4. The method as described in claim 1, characterized in that, In step S3, the system temperature under the heating and stirring conditions is maintained at 55°C to 65°C; the alkaline regulator is ammonia water, which is used to precisely adjust the pH value of the system to 5.0 to 5.5, and the system is continuously stirred at the specified temperature for 2 to 3 hours to carry out the alkaline catalytic polycondensation reaction.

5. The method as described in claim 4, characterized in that, In step S3, the total amount of lightly calcined magnesium oxide powder added is 25% to 42% of the mass of silicon dioxide contained in the initial silicon source aqueous solution, and the particle size of the lightly calcined magnesium oxide powder is sieved through a 200-mesh sieve.

6. The method as described in claim 1, characterized in that, In step S4, the aging treatment conditions are as follows: the gel that has undergone gelation transformation is placed in an environment of 55°C to 65°C and aged for 12 to 18 hours; after aging treatment, the specific surface area of ​​the silica mesoporous gel is stable at 180 m² / g to 280 m² / g, and its mesopore size is distributed between 4 nm and 8 nm.

7. The method as described in claim 1 or 6, characterized in that, In step S4, the drying process includes: first, breaking up the aged gel and then pre-drying it at 60°C for 6 to 8 hours, then raising the temperature to 105°C and drying it to constant weight, and finally pulverizing it to obtain composite conditioner dry powder.

8. The method as described in claim 7, characterized in that, In step S4, the granulation process includes: uniformly premixing sodium carboxymethyl cellulose dry powder with the composite conditioner dry powder, wet granulating in a granulator using deionized water as a wetting agent, drying, and then sieving to obtain granules with a particle size of 2 mm to 4 mm; wherein, the total amount of sodium carboxymethyl cellulose solid is controlled to be 1% to 3% of the mass of the composite conditioner dry powder.

9. The method as described in claim 1, characterized in that, In step S5, the application of fertilizer into the acidic tobacco-growing soil includes two fertilization stages: the first stage is the application of base fertilizer, which is carried out 7 to 10 days before the tobacco transplanting, by evenly spreading the conditioner granules on the ground surface and rotary tilling them into the topsoil layer at a depth of 0 to 20 cm; the second stage is the application of topdressing, which is carried out 30 days after the tobacco transplanting, during the seedling stage, by opening furrows between the tobacco rows to apply the conditioner granules and backfilling them with soil.

10. The method as described in claim 9, characterized in that, The amount of base fertilizer applied in the first stage is 40 kg to 60 kg per mu; the amount of topdressing applied in the second stage is 15 kg to 20 kg per mu. No additional silicon fertilizer or micronutrient inorganic salt fertilizer should be applied during the entire growth period.